ESTIMATION OF WORKING CONDITIONS OF FOUNDRY WORKERS BY INFRARED (HEAT) RADIATION - A. M. Lazarenkov; S. A. Horeva (Литьë и металлургия)
The description of infrared radiations, their influence on human organism is given. The results of investigation of infrared (heat) radiation intensity on the workers in foundries are given.